Anthropomorphic and zoomorphic images on the Neolithic and Eneolithic objects in the collection of the Kostroma State Historical, Architectural and Art Museum-Reserve - Anton V. Shipilov (Археология евразийских степей)
The article deals with a complex of archaeological sources belonging to the art of the Neolithic and Eneolithic periods. Art objects are striking and relatively rare category of finds at the Neolithic–Eneolithic settlement sites in the Kostroma Volga region. A wide variety of images were widespread in the spiritual culture and beliefs of the ancient population of the Kostroma region. The archaeological sources of the Neolithic and Eneolithic, which are in the collection of the Kostroma State Historical, Architectural and Art Museum-Reserve, give a definite idea of them. They display zoomorphic and anthropomorphic images, which were probably widespread in the spiritual culture of the population of the Upper Volga region in the era of stone and early metal. The purpose of this article is to replenish the source base on the prehistoric art and spiritual culture of the ancient population of the Eastern Europe forest belt.